Applications of Alternating Current/Alternating Potential Electrolysis in Organic Synthesis - Jamshidi, Mahdi; Fastie, Cornelius; Hilt, Gerhard (Synthesis, 2022)
This review summarises the rarely used method of alternating current electrolysis for the synthesis of organic products. Different waveforms have been investigated which opens the possibility for further influence the outcome of the electrolysis by variation of the frequency as well as the highest peak current. In recent years alternating current electrolysis has been applied in increasingly more complex transformations. Especially the functionalisation of (hetero)arenes, functional group manipulation, metathesis reactions, and transition-metal-catalysed cross-coupling reactions were reported in recent years and the results of these and some other investigations are summarized in this review article.1 Introduction1.1 Waveforms1.2 Objectives1.3 Early Examples of the Optimisation of Alternating Current Electrolysis2 Recent Applications of Alternating Current Electrolysis for Organic Synthesis2.1 Substitution Reaction on Arenes2.2 Nitrogen–Sulfur Bond Formation and Sulfur–Sulfur Bond Metathesis2.3 Oxidation and Reduction2.4 Cross-Coupling Reactions2.5 Frequency Optimisation3 Conclusion
Keywords: alternating current; alternating polarity; electrochemistry; organic synthesis; reactive intermediates